Selective non-operative management of abdominal gunshot wounds at Groote Schuur Hospital : a cohort study of clinical outcomes and financial costs - Kim, Rebecca Y (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 57-59).